The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1614/ipsm-d-11-00020.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chinese Privet (Ligustrum sinense) on Decomposition and Nutrient Availability in Riparian Forests

Abstract: As invasive species become increasingly abundant in forests, their presence may influence a number of key nutrient cycling processes. For example, Chinese privet has become well established in southeastern forests and continues to spread. Two studies, a multisite field investigation and a controlled approach on a single site, were conducted to examine the role of Chinese privet (Ligustrum sinense) on decomposition within riparian forests of the Georgia Piedmont. The field study also investigated the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 35 publications
(47 reference statements)
2
37
1
1
Order By: Relevance
“…For example, Stone (1997) has shown that practicing site preparation procedures such as hand-pulling seedlings and mowing and/or cutting stems larger than 2.5 m can successfully reduce Chinese privet invasion in relatively small areas, such as nature preserves [29]. Chinese privet has been shown to inhibit reproduction and growth of trees through altering the occurrence of arbuscular mycorrhizal fungi in the resident soil [30] and influencing a number of key nutrient cycling processes [31]. In addition, a combination of shading and some allelopathic effect of adult leaf leachate inhibit the growth of other plants under a canopy of Chinese privet and contribute to a reduction in plant diversity after invasion [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Stone (1997) has shown that practicing site preparation procedures such as hand-pulling seedlings and mowing and/or cutting stems larger than 2.5 m can successfully reduce Chinese privet invasion in relatively small areas, such as nature preserves [29]. Chinese privet has been shown to inhibit reproduction and growth of trees through altering the occurrence of arbuscular mycorrhizal fungi in the resident soil [30] and influencing a number of key nutrient cycling processes [31]. In addition, a combination of shading and some allelopathic effect of adult leaf leachate inhibit the growth of other plants under a canopy of Chinese privet and contribute to a reduction in plant diversity after invasion [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has become widely naturalized in the southeastern United States and is reported to have invaded thousands of acres (Mitchell et al 2011;Ward 2002). It generally has multiple stems and a shrub-like growth form, with heights ranging from 1.5 to 3.6 m (5 to 12 ft), although it occasionally becomes treesized (Greene and Blossey 2011).…”
mentioning
confidence: 99%
“…Much of the previous research on CHP has focused on growth characteristics, response to flooding, dispersal rates, impacts on native plants and forest regeneration, and influences on decomposition and nutrient availability (Hanula et al 2009;Merriam and Feil 2002;Mitchell et al 2011;Morris et al 2002). Research in the Piedmont region of the United States has indicated that CHP invasion suppresses herbaceous understory, causing decreases in plant species richness and diversity (Greene and Blossey 2011;Merriam and Feil 2002;Wilcox and Beck 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations